Speciation, evolutionary history and conservation trends of neotropical deer - González, Susana (2020)
Neotropical deer species have broad geographic ranges in vulnerable Latin American ecosystems. Habitat destruction and overhunting have limited deer species to a portion of their historical ranges. Our aims are to provide an overview of the current state of knowledge of Neotropical deer species systematics and evolutionary history, and to discuss their current conservation status. Genetic methods lead to a reassessment of earlier systematics, largely based only on morphological analyses, and revealed several cryptic species. Neotropi-cal deer species show substantial karyotypic variation from 2n = 32 to 2n = 70. Moreover, several species with chromosomal polymorphisms and complex karyotypes have been described in the genus Mazama. Analysis of the complete cytochrome b gene revealed two clades with different evolutionary histories. Mazama and Hip-pocamelus are not monophyletic genera, and both genera include cryptic species. At least two new red brocket deer species need to be described and their geographic range and population status assessed. Based on the latest IUCN Red List of Threatened Species™ 59% of the 17 Neotropical deer species are threatened and 12% are listed as Data Deficient (DD). The contribution of genetic and biogeographic data will be useful for solving taxonomic uncertainties and updating the assessment of the conservation status of species in Latin American ecosystems, providing data to perform models for testing management and conservation policies.